Elucidating the gut microbiota-driven crosstalk: mechanistic interplay of lobetyolin in coordinating cholesterol homeostasis and anti-inflammatory pathways in hyperlipidemic mice models - Duan, Guofeng; Zhang, Yuning; Liu, Siyuan; Wang, Siqi; Liu, Jinjia; Li, Lijuan; Lai, Lina (Frontiers in Microbiology, 2025)
BackgroundHyperlipidemia is a prevalent metabolic disorder closely associated with gut microbiota imbalance. In recent years, traditional Chinese medicine has demonstrated distinct advantages in the regulation of the gut microbiota and enhancement of metabolic health. This study aimed to elucidate the molecular processes by which lobetyolin modifies the gut microbiota to improve intestinal inflammation and lipid metabolism in hyperlipidemic mice.MethodsForty female KM mice were randomly allocated to four groups: control, model, LBT1, and LBT2. Mice in the LBT1 and LBT2 groups received intraperitoneal injections of the corresponding concentrations of LBT for ten consecutive days, whereas mice in the control and model groups received intraperitoneal injections of physiological saline. Beginning on the eighth day, mice in the model, LBT1, and LBT2 groups received subcutaneous injections of Triton WR-1339 for three consecutive days, whereas those in the control group received subcutaneous injections of physiological saline concurrently. On the eleventh day of the experiment, serum, liver, colon, and fecal samples were collected from all mice. This study aimed to measure lipid metabolism in mouse serum and liver, assess the inflammatory status of the mouse colon, and evaluate changes in the gut microbiota.ResultsLobetyolin significantly reduced the levels of triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), and total cholesterol (T-CHO) in the serum of hyperlipidemic mice. Concurrently, it elevated the levels of high-density lipoprotein cholesterol (HDL-C). The mechanism involves the reduction of endogenous cholesterol production and promotion of reverse cholesterol transport. LBT can also alleviate inflammatory responses by inhibiting the TLR4/NF-κB signaling pathway. In addition, it can regulate the balance of Th1 and Th2 immunity and enhance the immune capacity of the colon mucosa. According to the results of 16S rRNA sequencing, LBT increased the abundance of beneficial gut microbiota, such as Akkermansia, Dubosiella, and Lactobacillus, which were positively correlated with HDL-C, IL-10, IL-4, and SIgA but negatively correlated with T-CHO, TG, LDL-C, VLDL-C, IL-6, IFN-γ, and TNF-α.ConclusionOur findings emphasize that lobetyolin exerts lipid-lowering and anti-inflammatory effects by regulating the ecological structure of the gut microbiota.